Risk assessment of azo dyes as food additives: Revision and discussion of data gaps toward their improvement. Issue 1 (14th November 2022) - Ramos‐Souza, Caroline; Bandoni, Daniel Henrique; Bragotto, Adriana Pavesi Arisseto; De Rosso, Veridiana Vera
Abstract: The food industry uses dyes mainly to overcome color loss during the processing and storage of products, with the azo dyes currently being the most employed. Studies on the safety of using these dyes in foods started in the 1950s and have indicated the potential for concern. This review discusses the risk assessment of food intake containing artificial azo dyes. There are case reports and, subsequently, double‐blind placebo‐controlled trials in some individuals who may experience adverse effects from the intake of azo dyes, but it is unclear whether these adverse effects are restricted to specific populations or more generalized. In view of this, different toxicological endpoints are evaluated to verify toxic effects in in vitro and in vivo models and to establish the no observed adverse effect level. Exposure estimation studies have shown that human exposure to azo dyes via oral intake is mainly below the acceptable daily intake established by advisory bodies. However, most countries do not have studies that estimate the oral intake of azo dyes. In this case, local food diversity and racial–ethnic specificities are not considered when stating the exposure estimate is below the acceptable daily intake for the human population and thus may not represent actual intake. Concerning the scenario established above, this review discusses the most critical gaps to be overcome to contribute to the direction of future studies and the development of more effective public policies concerning the safety of the intake of artificial azo dyes.